HUBUNGAN SPIRITUALITAS DENGAN TINGKAT KECEMASAN MENGHADAPI MASA TUA PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA - Khairani, Wittin; Sepalanita, Widya; Purwanti, Nunuk Sri (Jurnal Medikes (Media Informasi Kesehatan), 2023)
The forms of problems in old age are problems at work, as well as problems in loneliness, interest and isolation, as well as disinhibition (inability or unwillingness), moods that are always changing, and the role of faith. All these problems occur because of financial uncertainty, job uncertainty or not getting a job opportunity, uncertainty due to neglect of children, uncertainty due to environmental neglect, fear of deteriorating health, fear of death, lack of dhikr and pray to Allah SWT, loss of people and closest friends. This study aims to determine the relationship between spiritual status and anxiety level in facing old age in the elderly at Tresna Werdha Budi Luhur Social Institution. This type of research is an analytic descriptive study using a cross sectional design. The population in this study were all 69 elderly people at the Tresna Werdha Institution. The sampling technique by means of purposive sampling technique. The results of this study indicate that the 41 respondents, the majority of respondents (51.2%) have poor spirituality in dealing with old age. The description of anxiety in facing old age shows that the majority of respondents (68.3%) have severe anxiety. There is a relationship between spirituality and anxiety levels. It is suggested that in carrying out gerontic nursing practice so that it can equip the elderly in facing old age with something that creates peace of mind and soul. One of them is by increasing spirituality to eliminate anxiety in the elderly in facing old age. As an effort to carry out the responsibilities and duties as a health service provider to prevent, maintain, recover, treat and improve the health status of the community.